Low Expression of YTH Domain-Containing 1 Promotes Microglial M1 Polarization by Reducing the Stability of Sirtuin 1 mRNA - Zhou, Hongxiu; Xu, Zongren; Liao, Xingyun; Tang, Shiyun; Li, Na; Hou, Shengping (Frontiers in Cellular Neuroscience, 2021)
The N6-methyladenosine (m6A) modification is the most abundant posttranscriptional mRNA modification in mammalian cells and is dynamically modulated by a series of "writers", "erasers" and "readers". Studies have shown that m6A affects RNA metabolism in terms of RNA processing, nuclear export, translation, and decay. However, the role of the m6A modification in retinal microglial activation remains unclear. Here, we analyzed the single-cell RNA sequencing data of retinal cells from mice with uveitis and found that the m6A-binding protein YTH domain-containing 1 (YTHDC1) was significantly downregulated in retinal microglia in the context of uveitis. Further studies showed that YTHDC1 deficiency resulted in M1 microglial polarization, an increased inflammatory response and the promotion of microglial migration. Mechanistically, YTHDC1 maintained sirtuin 1 (SIRT1) mRNA stability, which reduced signal transducer and activator of transcription 3 (STAT3) phosphorylation, thus inhibiting microglial M1 polarization. Collectively, our data show that YTHDC1 is critical for microglial inflammatory response regulation and can serve as a target for the development of therapeutics for autogenic immune diseases.